Implementation of Differentiated Learning Using the Inquiry Based Learning (IBL) Learning Model to Improve Students' Critical Thinking Abilities - Fani Rasma Sari; Agus Suyatna; Dimas Permadi (Master of Physics Education Study Programme, 2025)
This study aims to determine the effect of differentiated learning process using the IBL learning model on improving students' critical thinking ability at each initial ability and to determine the differences in critical thinking ability that may be caused by initial abilities. The sample in this study were students of class X1 and X2 of SMAN 1 Sekampung in the 2024/2025 academic year. This research design uses One Group Pretest Posttest Design. The research instrument uses essay questions with critical thinking ability indicators. The results of this study indicate that there is a difference in the pretest and posttest scores of students where the posttest score is greater than the pretest score, thus it can be stated that there is an increase in students' critical thinking ability. In addition, the N-gain value obtained is greater than 0.05 which states that there is no difference in students' critical thinking ability based on the initial ability group.